Lignans of sesame (Sesamum indicum L.): A comprehensive review - Andargie, Mebeaselassie (2021)
Major lignans of sesame sesamin and sesamolin are benzodioxol–substituted furofurans. Sesamol, sesaminol, its epimers, and episesamin are transformation products found in processed products. Synthetic routes to all lignans are known but only sesamol is synthesized industrially. Biosynthesis of furofuran lignans begins with the dimerization of coniferyl alcohol, followed by the formation of dioxoles, oxidation, and glycosylation. Most genes of the lignan pathway in sesame have been identified but the inheritance of lignan content is poorly understood. Health-promoting properties make lignans attractive components of functional food. Lignans enhance the efficiency of insecticides and possess antifeedant activity, but their biological function in plants remains hypothetical. In this work, extensive literature including historical texts is reviewed, controversial issues are critically examined, and errors perpetuated in literature are corrected. The following aspects are covered: chemical properties and transformations of lignans; analysis, purification, and total synthesis; occurrence in Seseamum indicum and related plants; biosynthesis and genetics; biological activities; health-promoting properties; and biological functions. Finally, the improvement of lignan content in sesame seeds by breeding and biotechnology and the potential of hairy roots for manufacturing lignans in vitro are outlined.